COMPREHENSIVE ANALYSIS OF STUDENTS’ AND TEACHERS’ ATTITUDES TOWARDS EFFECTS OF AI (ARTIFICIAL INTELLIGENCE) ON HIGHER EDUCATION: A MIXED APPROACH - Istamova, Shahnoza Ismoil kizi; Khasanova, Yulduz Mukhtor kizi (Innovative Development in Educational Activities, 2024)
Artificial Intelligence (AI) is cropping up day by day as an essential part of our developing era. This research paper illustrates a comprehensive analysis of the impacts of AI on higher education finding its alternative influences on educating, learning, and the overall education system. Drawing on recent developments and findings, this paper highlights some positive and negative sides of the usage of AI and the teachers’ and students’ views on the role of AI and its effects on their work and study. Firstly, the article begins by providing background information about AI like its meaning, main aim, and types. Then, other researchers’ opinions and works about AI have been studied. It mentions the advantages and disadvantages of AI and some changes in the education landscape by showing some data about tutoring systems, automated assessment tools, and adaptive learning platforms. Secondly, the survey was conducted to check people’s concepts whose work is related to education about AI. In the survey, although AI is being one of the main tools in education, there are still some people who do not have background data about AI. Because of these sorts of misunderstandings of teachers about AI, students are using AI in order to accomplish their tasks by plagiarizing. Finally, studying all the information and research, the views of the targeted population of the survey were discussed. Most of them responded that AI plays a crucial role in education according to its benefits like time-saving, getting reliable information in a short time, and getting feedback.